An investigation of the individual and combined effects of methylprednisolone and heparin treatment, prior to and after induction of disseminated intravascular coagulation (DIC) with thrombin, in baboons - Du Toit, Hendrik Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1988.